The ‘Extra’ Dimension in the Theology of Calvin - Oberman, Heiko A. (The journal of ecclesiastical history, 1970)
If it is true that the built-in principle of radical self-criticism is one of the marks of the Reformation tradition, contemporary students of Reformation thought have a valid claim upon their place in its authentic succession. Though more slowly and with occasional relapses into an earlier stance of confessional apologetics, this applies increasingly also to studies dealing with the relation of the theology of Luther and Calvin.